I'm trying to prove that the following series

$$\sum_{n=1}^{\infty}(-1)^n \dfrac{x^2 + n}{n^2}$$

converges uniformly on every finite interval $I$ in $\mathbb{R}$.

In the previous exercice I've shown that the series is not absolute convergent for any $x \in \mathbb{R}$, so this might be of use, but I'm not sure how.

I've attempted to use the Weierstrass M-test and tried to find some $M_n \geq \dfrac{x^2 + n}{n^2} \; \forall x \in I$ such that $\sum M_n$ converges. But I realised that this would imply that $M_n \geq \frac{1}{n}$ and thus $\sum M_n$ cannot converge.

I also tried finding the partial sums for the series, but this also turned out to be pretty tough.

How would I go about showing uniform convergence on $I$?


2 Answers 2


First given $x \in \mathbb{R}$:

$$\sum_{n=1}^{\infty}(-1)^n \dfrac{x^2 + n}{n^2}=\sum_{n=1}^{\infty}(-1)^n \dfrac{x^2}{n^2}+\sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n}$$

So if you prove $\sum_{n=1}^{\infty}(-1)^n \dfrac{x^2}{n^2}$ is absolutly convergent you are ready (since the second sum converges and is constant and not depends on $x$).

$x^2$ is bounded for every finite interval on $I$ by $M_I$:

$$\left|(-1)^n\frac{x^2}{n^2}\right|\leq \frac{M_I}{n^2} $$

So $\sum_{n=1}^{\infty}(-1)^n \dfrac{x^2}{n^2}$ is absolutly convergent.

Uniformity: pointwise $f_m(x)$ converges to:

$$f(x)=x^2 \sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n^2}+\sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n}$$ So: $$|f(x)-f_m(x)|=$$ $$\left|x^2 \sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n^2}+\sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n}-x^2 \sum_{n=1}^{m}(-1)^n \dfrac{1}{n^2}-\sum_{n=1}^{m}(-1)^n \dfrac{1}{n}\right|$$ $$\leq\left|x^2 \sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n^2}-x^2 \sum_{n=1}^{m}(-1)^n \dfrac{1}{n^2}\right|+\left|\sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n}-\sum_{n=1}^{m}(-1)^n \dfrac{1}{n}\right|$$

$$\leq|x^2|\left| \sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n^2}- \sum_{n=1}^{m}(-1)^n \dfrac{1}{n^2}\right|+\left|\sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n}-\sum_{n=1}^{m}(-1)^n \dfrac{1}{n}\right|$$ $$\leq M_I\left| \sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n^2}- \sum_{n=1}^{m}(-1)^n \dfrac{1}{n^2}\right|+\left|\sum_{n=1}^{\infty}(-1)^n \dfrac{1}{n}-\sum_{n=1}^{m}(-1)^n \dfrac{1}{n}\right|$$

At that point you can complete the demostration (because the convergence is not given by the point $x$ you take)


Let $M>0$ such that $I \subset [-M,M]$

Let $$\begin{array}{ccccc} f & : & I & \to & \mathbb R \\ & & x & \mapsto & \sum_{n=1}^{\infty}(-1)^n \dfrac{x^2 + n}{n^2} \\ \end{array}$$

For $m\in \mathbb N$, let $$\begin{array}{ccccc} f_m & : & I & \to & \mathbb R \\ & & x & \mapsto & \sum_{n=1}^{m}(-1)^n \dfrac{x^2 + n}{n^2} \\ \end{array}$$

Now for $x \in I$, because the series is alternate, $$|f(x)-f_m(x)|\leq \dfrac{x^2 + n+1}{(n+1)^2} \leq \dfrac{M^2 + n+1}{(n+1)^2}$$

Because $\frac{M^2 + n+1}{(n+1)^2} \to 0$ and is independent on $x$, uniform convergence is granted.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.